Spatio-Temporal Determination of Small-Scale Vessels’ Fishing Grounds Using a Vessel Monitoring System in the Southeastern Gulf of Mexico - Torres-Irineo, Edgar; Salas, Silvia; Euán-Ávila, Jorge Iván; Palomo, Leopoldo E.; Quijano Quiñones, Daniel R.; Coronado, Eva; Joo, Rocío (Frontiers in Marine Science, 2021)
In most small-scale fisheries (SSF), there is limited or null information about the distribution and spatial extent of the fishing grounds where the fleets operate, due to the lack of explicit spatial and temporal data. This information is key when addressing marine spatial planning and fisheries management programs for SSF. In addition to technical or biogeographic restrictions, environmental conditions in the area influence the way fishers operate. Making use of data from a pilot Vessel Monitoring System (VMS) project tested in a small-scale fleet in the Southeastern Gulf of Mexico (SGoM), for the first time in the region, we were able to learn what role environmental factors play in the distribution of potential fishing grounds for this fleet. We got tracking information of 1,608 daily fishing trips from vessels operating in four states using the VMS for seven months. We used a correlative modeling approach to identify potential fishing grounds where this fleet operates along the SGoM, accounting for environmental variables. We assumed that environmental conditions can shape the spatial distribution of species targeted by this fleet and hence influence fishers’ operations. The results indicated that net primary production and sea surface temperature were the main drivers that shape the spatio-temporal potential distribution of fishing grounds in the study site. The approach employed here seems appropriated and opens an opportunity to learn more about the factors that define the spatial distribution of small-scale fleets and their potential fishing grounds.